Interferon-induced transmembrane protein 3 in the hippocampus: a potential novel target for the therapeutic effects of recombinant human brain natriuretic peptide on sepsis-associated encephalopathy - Li, Nan; Ma, Rui-Hang; Zhang, Er-Fei; Ge, Feng; Fang, De-Yu; Zhang, Jing; Zhang, Yan-Ning; Gao, Yan; Hou, Li-Chao; Jin, Hong-Xu (Frontiers in Molecular Neuroscience, 2023)
Objective This study aims to explore whether interferon-induced transmembrane protein 3 (IFITM3) is involved in recombinant human brain natriuretic peptide (rhBNP)-mediated effects on sepsis-induced cognitive dysfunction in mice.The cellular localization and expression level of IFITM3 in the hippocampus were detected. The IFITM3 overexpression was achieved using an intracranial stereotactic system to inject an adeno-associated virus into the hippocampal CA1 region of mice. Field experiments, an elevated plus maze, and conditioned fear memory tests assessed the cognitive impairment in rhBNP-treated septic mice. Finally, in the hippocampus of septic mice, terminal deoxynucleotidyl transferase biotin-dUTP nick end labeling (TUNEL) staining and Immunoblot were used to detect changes in the protein expression of cleaved Caspase-8 and cleaved Caspase-3 in apoptosis-related pathways, and toll-like receptor 4 (TLR4) and nuclear factor κ B (NF-κB) p65 in inflammatory pathways.Fourteen days after cecal ligation and puncture (CLP) surgery, IFITM3 localized in the plasma membrane and cytoplasm of the astrocytes in the hippocampus of septic mice, partially attached to the perivascular and neuronal surfaces, but not expressed in the microglia. The expression of IFITM3 was increased in the astrocytes and neurons in the hippocampus of septic mice, which was selectively inhibited by the administration of rhBNP. Overexpression of IFITM3 resulted in elevated anxiety levels and long-term learning and memory dysfunction, completely abolished the therapeutic effect of rhBNP on cognitive impairment in septic mice, and induced an increase in the number of neuronal apoptosis in the hippocampal CA1 region. The expression levels of cleaved Caspase-3 and cleaved Caspase-8 proteins were significantly increased in the hippocampus, but the expression levels of TLR4 and NF-κB p65 were not increased.The activation of IFITM3 may be a potential new target for treating sepsis-associated encephalopathy (SAE), and it may be one of the key anti-apoptotic mechanisms in rhBNP exerting its therapeutic effect, providing new insight into the clinical treatment of SAE patients.Keywords sepsis-associated encephalopathy (SAE), recombinant human brain natriuretic peptide (rhBNP), interferon-induced transmembrane protein 3 (IFITM3), inflammation, apoptosis